Enhanced sensitivity of the urban heat island effect to summer temperatures induced by urban expansion - Gao, Zhen; Hou, Ying; Chen, Weiping (Environmental research letters, 2019)
A suitable thermal environment is important for the economy, society and public health in urban areas. However, the understanding of the relationship between the urban heat island (UHI) effect and background temperature (T-UHI) is very limited. In this study, the UHI effect induced by the urbanization of the megacity Beijing was investigated using the weather research and forecasting model. Urban expansion and heatwaves both considerably enhanced the UHI effect over urban areas in summer. The strengthened UHI effect during the heatwave period can be clearly explained by the positive sensitivity of T-UHI. The urban expansion increased the sensitivity of T-UHI from 0.0207 °C °C−1 in 2000 to 0.0569 °C °C−1 in 2010 in the daytime and from 0.0715 °C °C−1 in 2000 to 0.0995 °C °C−1 in 2010 at nighttime, thus resulting in a much stronger UHI effect mainly by increasing the difference between the latent heat flux and sensible heat flux. This enhanced sensitivity may exacerbate the urban heat stress in the situation of further urban expansion and background climate warming. Our results suggest that the sensitivity of T-UHI is a meaningful indicator to assess the urban thermal environment change and support the designing of heat mitigation strategies in urban planning.